2018
DOI: 10.1016/j.joca.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the reliability and discriminative validity of cartilage compositional MRI in knee osteoarthritis

Abstract: Objective: To assess reliability and discriminative validity of cartilage compositional magnetic resonance imaging (MRI) in knee osteoarthritis (OA). Design: The study was carried out per PRISMA recommendations. We searched MEDLINE and EMBASE (1974 e present) for eligible studies. We performed qualitative synthesis of reliability data. Where data from at least two discrimination studies were available, we estimated pooled standardized mean difference (SMD) between subjects with and without OA. Discrimination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
87
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 94 publications
3
87
1
2
Order By: Relevance
“…It is known that T 2 is sensitive to water, collagen content, and tissue anisotropy . In MacKay et al, it is shown that T 2 is usually higher in knee OA patients, compared to healthy subjects, with significant differences between subjects (standardized mean difference of 0.49). The acceleration of T 2 mapping using CS was among the first applications for knee cartilage, where radial acquisition and PCA sparsity were used to demonstrate the possibility of reducing the acquisition time by 8 times, requiring 2 minutes and 17 seconds, with little loss compared to the gold standard …”
Section: Applications Of Cs‐mri To Compositional Mapping Of Knee Cartmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that T 2 is sensitive to water, collagen content, and tissue anisotropy . In MacKay et al, it is shown that T 2 is usually higher in knee OA patients, compared to healthy subjects, with significant differences between subjects (standardized mean difference of 0.49). The acceleration of T 2 mapping using CS was among the first applications for knee cartilage, where radial acquisition and PCA sparsity were used to demonstrate the possibility of reducing the acquisition time by 8 times, requiring 2 minutes and 17 seconds, with little loss compared to the gold standard …”
Section: Applications Of Cs‐mri To Compositional Mapping Of Knee Cartmentioning
confidence: 99%
“…For osteoarthritis (OA), a recent meta‐analysis validated the reliability (compiling 58 studies) and discriminative ability (compiling 26 studies) of cartilage compositional MRI mapping in the knee, where T 2 and T 1ρ relaxometry demonstrated discrimination validity in mild OA. This can help us to detect the early stages of OA …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). (26) Semiquantitative scoring Sagittal proton density fat saturated sequences (TR = automatic [approximately 4000 ms], TE = 30 ms, ETL/echoes = 8, slice thickness = 3 mm with no gap, FOV = 16 cm, matrix = 384 × 288, acquisition time = 4 min 58 s) were acquired of each knee during the same scanning session as the T2 maps. (24) Specifically, four regions of condylar cartilage were defined for the medial and lateral tibial and femoral condyles, using bony landmarks and lateral borders of the bones.…”
Section: Knee Joint Measuresmentioning
confidence: 99%
“…[12][13][14][15][16] T 1ρ is sensitive to the slow-motional interactions between local macromolecular environments and bulk water 17 and as a result to proteoglycan content in the tissue, 18 while T 2 is found to be sensitive to the collagen fibril orientation and anisotropy. 19,20 Furthermore, a recent meta-analysis 21 study validated the reliability (compiling 58 studies) and discriminative ability (compiling 26 studies) of T 1ρ and T 2 compositional mapping of knee cartilage, especially in mild knee OA as a motivation. T 1ρ showed better discrimination for mild OA and OA compared to T 2 .…”
mentioning
confidence: 95%